Lithium manganese iron phosphate and nickel cobalt lithium manganate composite positive electrode material, preparation method thereof, positive electrode and battery
By using vacuum environment and ultrasonic treatment methods in the preparation of lithium-ion battery positive electrode materials, the stability problems caused by ordinary mechanical stirring are solved, and the uniform dispersion of the positive electrode materials and the improvement of battery performance are achieved.
Patent Information
- Application Number
- CN202411913813.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-24
AI Technical Summary
When using the mixture of nickel-cobalt lithium manganese oxide and lithium manganese iron phosphate as the positive electrode material of lithium-ion batteries in the prior art, there is a risk of poor stability in the ordinary mechanical stirring method, which affects the performance of the battery.
A composite positive electrode material preparation method including vacuum environment and ultrasonic treatment is adopted. By adding conductive agents such as carbon nanotubes and SP in stages, the particles are evenly dispersed and agglomerated.
The stability and uniformity of the positive electrode material are achieved, the energy density and safety of the battery are improved, and the electrochemical impedance of the battery during the cycle is reduced.
Smart Images

Figure CN119812251A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a composite positive electrode material of lithium iron manganese phosphate and lithium nickel cobalt manganese oxide, and a preparation method thereof, a positive electrode, and a battery. Background Art
[0002] The positive electrode materials in lithium-ion batteries are divided into lithium iron phosphate, lithium iron manganese phosphate, and nickel cobalt manganese oxide materials. Among them, lithium iron manganese phosphate positive electrode materials have a stable structure, are not prone to structural collapse during charging and discharging, have better safety, lower cost, and long life. The cycle life can reach more than 2,000 times, which is higher than that of ternary lithium batteries. However, lithium iron manganese phosphate has a higher cost and lower energy density. Ternary materials have higher energy density and rate performance, but ternary materials have poor safety and fewer nickel and cobalt resources, and the cost of using materials is higher.
[0003] Mixing lithium nickel cobalt manganese oxide and lithium iron manganese phosphate as positive electrode materials for lithium-ion batteries can combine the advantages of these two materials, optimize the overall performance of the battery, improve the energy density and cycle stability of the battery, and provide solutions to the problems of low conductivity of lithium iron manganese phosphate materials and slow lithium ion diffusion rate. In the prior art, lithium nickel cobalt manganese oxide and lithium iron manganese phosphate are usually mixed by ordinary mechanical stirring as positive electrode materials. However, the preparation of positive electrode mixed materials by ordinary mechanical mixing has the risk of poor stability, which in turn affects battery performance. Summary of the invention
[0004] In order to solve the above problems, the present application provides a composite positive electrode material of lithium manganese iron phosphate and nickel cobalt manganese oxide with good stability, a preparation method thereof, a positive electrode, and a battery. The present application adopts the following technical solutions:
[0005] The first aspect of the present application discloses a method for preparing a composite positive electrode material of lithium iron manganese phosphate and lithium nickel cobalt manganese oxide, the preparation method comprising: preparing raw materials, the raw materials comprising active materials, conductive agents, binders and solvents, the active materials comprising lithium iron manganese phosphate and lithium nickel cobalt manganese oxide, the conductive agents comprising carbon nanotubes and SP; preparing a first solution, mixing the binder and the solvent to obtain a first solution; preparing a first mixed material, adding the carbon nanotubes to the first solution for mixing, to obtain the first mixed material; preparing a second mixed material, mixing lithium iron manganese phosphate and lithium nickel cobalt manganese oxide to obtain the second mixed material; preparing a third mixed material, mixing the second The mixed material and SP are mixed to obtain the third mixed material; prepare the fourth mixed material: add the first mixed material to the third mixed material, mix them evenly, and obtain the fourth mixed material, that is, the positive electrode material; wherein: at least one step of preparing the first solution, preparing the first mixed material, preparing the second mixed material, preparing the third mixed material and preparing the fourth mixed material is carried out in a vacuum environment; in at least one step of preparing the first solution, preparing the first mixed material, preparing the second mixed material, preparing the third mixed material and preparing the fourth mixed material, mixing is performed by ultrasonic treatment.
[0006] In one implementation of the present application, the vacuum degree of the vacuum environment is -5MPa to -1MPa.
[0007] In one implementation of the present application, the frequency of the ultrasound is 10 kHz to 20 kHz.
[0008] In one implementation of the present application, in the step of preparing the fourth mixed material, the first mixed material is added to the third mixed material in 2 to 4 batches.
[0009] In one implementation of the present application, in at least one of the steps of preparing the first solution, preparing the first mixed material, preparing the second mixed material, preparing the third mixed material and preparing the fourth mixed material, mixing is also performed by stirring, and the stirring rate is 1000rpm to 4000rpm, and the processing time is 0.1h to 3.5h.
[0010] In one implementation of the present application, a double planetary agitator is used for stirring, with an orbital speed of 5 to 50 rpm and a rotational speed of 1000 to 4000 rpm.
[0011] In one implementation of the present application, the mass ratio of the lithium manganese iron phosphate to the lithium nickel cobalt manganese oxide is 1:9 to 9:1, the D50 of the lithium manganese iron phosphate is 1 to 5 μm, and the D50 of the lithium nickel cobalt manganese oxide is 5 to 20 μm.
[0012] The second aspect of the present application discloses a positive electrode material, which is prepared by the preparation method disclosed in the first aspect of the present application.
[0013] The third aspect of the present application discloses a positive electrode, which includes a positive electrode collector and a positive electrode material as disclosed in the second aspect of the present application and attached to the positive electrode collector.
[0014] The fourth aspect of the present application discloses a battery, which includes the positive electrode disclosed in the third aspect of the present application.
[0015] The beneficial effects of this application are:
[0016] The lithium iron manganese phosphate and lithium nickel cobalt manganese oxide composite positive electrode material of the present application has no agglomeration phenomenon, can be coated on the surface of the pole piece more evenly, has good adhesion, and the battery has good energy density and safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a surface morphology diagram of the positive electrode sheet of Example 1 of the present application. DETAILED DESCRIPTION
[0018] The present invention is further described in detail below by specific embodiments in conjunction with the accompanying drawings. In the following embodiments, many detailed descriptions are intended to enable the present application to be better understood. However, those skilled in the art can effortlessly recognize that some of the features can be omitted in different situations, or can be replaced by other materials and methods. In some cases, some operations related to the present application are not shown or described in the specification, in order to avoid the core part of the present application being overwhelmed by too much description, and for those skilled in the art, it is not necessary to describe these related operations in detail, and they can fully understand the related operations according to the description in the specification and the general technical knowledge in the art.
[0019] In addition, the features, operations or characteristics described in the specification can be combined in any appropriate manner to form various implementations. At the same time, the steps or actions in the method description can also be interchanged or adjusted in a manner that is obvious to those skilled in the art. Therefore, the various sequences in the specification and the drawings are only for the purpose of clearly describing a certain embodiment and are not meant to be a required sequence, unless otherwise specified that a certain sequence must be followed.
[0020] The serial numbers assigned to the components in this article, such as "first", "second", etc., are only used to distinguish the objects described and do not have any order or technical meaning.
[0021] Mixing lithium nickel cobalt manganese oxide and lithium iron manganese phosphate and using them as positive electrode materials for lithium-ion batteries can combine the advantages of the two materials, optimize the overall performance of the battery, improve the energy density and cycle stability of the battery, and provide solutions to problems such as the low electrical conductivity of the lithium iron manganese phosphate material itself and the slow diffusion rate of lithium ions. In the prior art, the use of lithium nickel cobalt manganese oxide and lithium iron manganese phosphate as positive electrode materials is usually mixed by ordinary mechanical stirring. However, the preparation of positive electrode mixed materials by ordinary mechanical mixing has the risk of poor stability, which in turn affects battery performance. In view of this, the present application creatively proposes a composite positive electrode material of lithium iron manganese phosphate and nickel cobalt manganese oxide and a preparation method thereof. The present application has the following advantages:
[0022] (1) Adding the first mixed material to the third mixed material in several steps can stabilize the separated particles, prevent the particles from agglomerating again, and make the dispersion more uniform. The high-speed rotating stirring paddle uses the friction between the surface inclined at a certain angle and the material to make the material move tangentially along the paddle surface. At the same time, due to the action of centrifugal force, the material is thrown to the inner wall of the mixing chamber and rises along the wall. When it rises to a certain height, it falls back to the center of the impeller due to gravity and is then thrown up again. This combination of rising motion and tangential motion actually puts the material in a continuous spiral motion state. Due to the high speed of the paddle, the material movement speed is also very fast. The fast-moving particles collide and rub against each other, causing the particles or the clumps that are suspected to be gathered together to be broken. At the same time, the temperature of the material also rises accordingly, which is conducive to the adsorption of various additives by the powder.
[0023] (2) By adding the first mixed material (liquid) to the third mixed material (solid), the amount of the first mixed material added in steps can be adjusted, and a suitable amount can achieve a better kneading effect.
[0024] (3) Ultrasonic technology is added during the preparation process. The growth and rupture of bubbles generated by ultrasound can impact and disperse the agglomerates in the mixed material, and can also cause the material to flow at the macro level, making the mixing more uniform. Specifically, at the micro level, continuous ultrasonic vibration is used during the preparation process, so that a large number of bubbles are generated inside the material during the mixing process. The bubbles float upward and grow. When the bubble size reaches a certain critical value, the bubble growth rate increases rapidly, and then it ruptures instantly, forming a shock wave to disperse the agglomerates in the material; at the macro level, it manifests as a salt-containing environment during the material mixing process, which is conducive to the discharge of gas in the material and prevents the gas in the material from affecting the subsequent coating quality.
[0025] (5) A vacuum environment is used during the preparation process, which is conducive to exhausting the gas in the material and preventing the gas in the material from affecting the subsequent coating quality.
[0026] (6) There is no agglomeration of the positive and negative electrode slurries, and they adhere to the electrode sheets more evenly, with good adhesion. The DCR is small during the battery cycle, and the battery safety performance is good.
[0027] The present application is introduced below in conjunction with the accompanying drawings and specific implementation methods.
[0028] The present application firstly relates to a method for preparing a composite positive electrode material of lithium iron manganese phosphate and lithium nickel cobalt manganese oxide.
[0029] In a specific embodiment, the preparation method of the composite positive electrode material of lithium manganese iron phosphate and lithium nickel cobalt manganese oxide comprises the following steps:
[0030] Step S1: preparing raw materials, including active materials, conductive agents, binders and solvents.
[0031] Step S2: preparing a first solution: mixing a binder and a solvent to obtain a first solution.
[0032] Step S3: preparing a first mixed material: adding carbon nanotubes into the first solution and mixing them.
[0033] Step S4: preparing a second mixed material: mixing lithium manganese iron phosphate and lithium nickel cobalt manganese oxide.
[0034] Step S5: preparing the third mixed material: mixing the second mixed material and SP.
[0035] Step S6: preparing a fourth mixed material: adding the first mixed material to the third mixed material, mixing them evenly, to obtain a fourth mixed material, namely, a positive electrode material.
[0036] In a specific embodiment, the steps of preparing the first mixed material and preparing the third mixed material may be performed in any order.
[0037] In a specific embodiment, the raw materials of the positive electrode material include an active substance, a conductive agent, a binder and a solvent.
[0038] In a specific embodiment, the active material includes lithium manganese iron phosphate and lithium nickel cobalt manganese oxide.
[0039] In a specific embodiment, the particle size D50 of the lithium manganese iron phosphate material is 1 to 5 μm, and the specific surface is 15 to 20 μm. 2 / g, density is 0.5-1g / cm 3 .
[0040] In a specific embodiment, the particle size D50 of the nickel-cobalt-lithium manganese oxide material is 5-20 μm.
[0041] In a specific embodiment, in the nickel cobalt manganese oxide material, the ratio of nickel element to the three elements of nickel, cobalt and lithium is 60% to 95%. For example, in the nickel cobalt manganese oxide, the ratio of nickel element to the three elements of nickel, cobalt and lithium is 60%, 65%, 70%, 75%, 80%, 85%, 90% or 95%. Preferably, in the nickel cobalt manganese oxide material, the ratio of nickel element to the three elements of nickel, cobalt and lithium is 80% to 95%.
[0042] In a specific embodiment, in the nickel cobalt lithium manganese oxide material, the ratio of nickel, cobalt and lithium is 9:0.5:0.5.
[0043] In a specific embodiment, the mass ratio of lithium manganese iron phosphate to lithium nickel cobalt manganese oxide may be 1:9 to 9:1. For example, the mass ratio of lithium manganese iron phosphate to lithium nickel cobalt manganese oxide may be 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2 or 9:1.
[0044] In a specific embodiment, the binder may be PVDF (polyvinylidene fluoride), the conductive agent may be CNT (carbon nanotube) or SP (SuperP), and the solvent may be NMP (N-methylpyrrolidone).
[0045] In a specific embodiment, at least one step of preparing the first solution, preparing the first mixed material, preparing the second mixed material, preparing the third mixed material, and preparing the fourth mixed material is performed in a vacuum environment.
[0046] In a specific embodiment, the steps of preparing the first solution, preparing the first mixed material, preparing the second mixed material, preparing the third mixed material, and preparing the fourth mixed material are all performed in a vacuum environment.
[0047] In a specific embodiment, the vacuum degree of the vacuum environment is -5MPa to 0MPa. For example, the vacuum degree of the vacuum environment may be -5MPa, -4MPa, -3MPa, -2MPa, -1MPa, -0.5MPa or 0MPa. Preferably, the vacuum degree of the vacuum environment is -5MPa to -1MPa. It should be noted that MPa is megapascals; the vacuum degree of the vacuum environment is -1MPa, which is approximately equal to minus 10 standard atmospheric pressures.
[0048] In a specific embodiment, the steps of preparing the first solution, preparing the first mixed material, preparing the second mixed material, preparing the third mixed material, and preparing the fourth mixed material include mixing by ultrasonic treatment.
[0049] In a specific embodiment, the steps of preparing the first solution, preparing the first mixed material, preparing the second mixed material, preparing the third mixed material, and preparing the fourth mixed material all include mixing by ultrasonic treatment.
[0050] In a specific embodiment, the frequency of ultrasound is 10kHz to 20kHz. For example, the frequency of ultrasound can be 10kHz, 11kHz, 12kHz, 13kHz, 14kHz, 15kHz, 16kHz, 17kHz, 18kHz, 19kHz or 20kHz.
[0051] In a specific embodiment, at least one of the steps of preparing the first solution, preparing the first mixed material, preparing the second mixed material, preparing the third mixed material, and preparing the fourth mixed material further includes mixing by stirring.
[0052] In a specific embodiment, the stirring rate is 1000 rpm to 4000 rpm, and the processing time is 0.1 h to 3.5 h.
[0053] In a specific embodiment, a double planetary agitator is used for stirring, with an orbital speed of 5 to 50 rpm and a rotation speed of 1000 to 4000 rpm.
[0054] In a specific embodiment, an ultrasonic-double planetary mixer is used to mix the materials.
[0055] In a specific embodiment, in the step of preparing the fourth mixed material, the first mixed material is added to the third mixed material in multiple times. In a specific embodiment, in the step of preparing the fourth mixed material, the first mixed material is added to the third mixed material in 2 to 4 times. The mass of the first mixed material added each time is 20% to 80% of its own mass.
[0056] In a specific embodiment, the method for preparing the positive electrode material further includes: adding a binder to the fourth mixed material and adjusting the viscosity to obtain the positive electrode material.
[0057] In a specific embodiment, the viscosity of the positive electrode material is 2500 MPa·s to 4000 MPa·s.
[0058] In a specific embodiment, the method for preparing the positive electrode material further includes: screening and / or removing iron from the fourth mixed material after adjusting the viscosity.
[0059] In a specific embodiment, the screening process includes filtering with a 200-mesh screen.
[0060] In a specific embodiment, the iron removal process includes using an iron removal device to stir the slurry to remove magnetic substances in the slurry.
[0061] In a specific embodiment, the steps of preparing the first solution, preparing the first mixed material, preparing the second mixed material, preparing the third mixed material, and preparing the fourth mixed material are all performed in an environment of 20°C to 35°C.
[0062] In a specific embodiment, in the step of preparing the first solution, an ultrasonic-double planetary agitator is used for dispersion, the dispersion speed is 30-50 rpm, the rotation speed is 2100-2300 rpm, the ultrasonic frequency is 10-20 kHz, and the time is 2.5-3.5 hours.
[0063] In a specific embodiment, in the step of preparing the first mixed material, an ultrasonic-double planetary agitator is used for dispersion, the dispersion speed is 20-40 rpm, the rotation speed is 2500-3500 rpm, the ultrasonic frequency is 10-20 kHz, and the time is 0.5-1.5 h.
[0064] In a specific embodiment, in the step of preparing the second mixed material, an ultrasonic-double planetary agitator is used for dispersion, the dispersion speed is 5-15 rpm, the rotation speed is 100-200 rpm, the ultrasonic frequency is 10-20 kHz, and the time is 5-30 min.
[0065] In a specific embodiment, in the step of preparing the third mixed material, an ultrasonic-double planetary agitator is used for dispersion, the dispersion speed is 10-30 rpm for revolution, 200-300 rpm for rotation, the ultrasonic frequency is 10-20 kHz, and the time is 1-2 hours.
[0066] In a specific embodiment, in the step of preparing the fourth mixed material, an ultrasonic-double planetary agitator is used for dispersion, the dispersion speed is 30-50 rpm, the rotation speed is 1000-2000 rpm, the ultrasonic frequency is 10-20 kHz, and the time is 1.5-4 hours.
[0067] In a specific embodiment, in the step of preparing the fourth mixed material, 60-80% of the first mixed material is first added to the third mixed material, and an ultrasonic-double planetary agitator is used for dispersion, and the dispersion speed is 30-50 rpm, 1400-1600 rpm, and the ultrasonic frequency is 10-20 kHz, and the time is 1.5-2.5 hours. Then, 20-40% of the first mixed material is added to the third mixed material, and an ultrasonic-double planetary agitator is used for dispersion, and the dispersion speed is 30-50 rpm, 1100-1300 rpm, and the ultrasonic frequency is 10-20 kHz, and the time is 0.5-1.5 hours to obtain a fourth mixed material.
[0068] In a specific embodiment, the solid content of the first mixed material is 3% to 5%.
[0069] In a specific embodiment, the positive electrode material has a solid content of 55% to 60%, a viscosity of 2500 to 4000 MPa.s, and a fineness of ≤15 μm.
[0070] In a specific embodiment, in the positive electrode material, by weight, PVDF: NMP: CNT: SP: lithium manganese iron phosphate: lithium nickel cobalt manganese oxide = 0.1-1: 10-30: 10-30: 0.5-3: 30-80: 20-70.
[0071] The present application also relates to a positive electrode material prepared by the above-mentioned preparation method.
[0072] The present application also relates to a positive electrode, which comprises a positive electrode current collector and a positive electrode material attached to the positive electrode current collector, and the positive electrode material is the positive electrode material prepared by the above-mentioned preparation method.
[0073] The present application also relates to a battery, which comprises the positive electrode mentioned above.
[0074] The present application is further described in detail below by specific examples. The following examples are only further described for the present application and should not be construed as limiting the present application. It should be noted that the reagents, test kits, instruments, etc. used in the examples are all commercially available, and the operating steps are carried out according to the instructions or the general operating steps in the art.
[0075] Embodiment 1:
[0076] 1) PVDF and NMP were mixed and dispersed using an ultrasonic-double planetary agitator at a dispersion speed of 40 rpm, 2200 rpm, an ultrasonic frequency of 15 kHz, a time of 3 h, a temperature of 25° C., and a vacuum degree of -1 MPa to obtain a material.
[0077] 2) Add CNT to material A, with a dispersion speed of 30 rpm, 3000 rpm, an ultrasonic frequency of 15 kHz, a time of 1 h, a temperature of 25° C., and a vacuum degree of -1 MPa to obtain material B.
[0078] 3) Mix lithium manganese iron phosphate and 9-series nickel cobalt lithium manganese oxide, with a dispersion speed of 10 rpm, 150 rpm, an ultrasonic frequency of 15 kHz, a time of 30 min, a temperature of 25° C., and a vacuum degree of -1 MPa to obtain material C.
[0079] 4) SP was added to material C at a dispersion speed of 20 rpm, 200 rpm, an ultrasonic frequency of 15 kHz, a time of 1.5 h, a temperature of 25° C., and a vacuum degree of -1 MPa to obtain material D.
[0080] 5) Add 70% of material B to material D, with a dispersion speed of 40 rpm, 1500 rpm, an ultrasonic frequency of 15 kHz, a time of 2 h, a temperature of 25° C., and a vacuum degree of -1 MPa to obtain material E.
[0081] 6) Add 30% of material B to material E, with a dispersion speed of 40 rpm, 1200 rpm, an ultrasonic frequency of 15 kHz, a time of 1 h, a temperature of 25° C., and a vacuum degree of -1 MPa to obtain material F.
[0082] 7) Add appropriate amount of NMP to material F to adjust the viscosity of material F to 2500-4000 mPa.s to obtain material G.
[0083] 8) Using a 200-mesh screen, sieve material G under a vacuum condition of -0.01 mPa, and then stir the slurry using an iron removal device.
[0084] Among them, in terms of weight, in the positive electrode material, PVDF: NMP: CNT: SP: lithium manganese iron phosphate: lithium nickel cobalt manganese oxide (the ratio of the three elements of nickel, cobalt and lithium is 9:0.5:0.5) = 0.55:15.5:15:1:60:40.
[0085] Then, a negative electrode material is prepared: CMC, water, CNT, conductive glue, graphite, SP and SBR are evenly mixed to obtain a negative electrode material, wherein, by weight, CMC: water: CNT: conductive glue: graphite: SP: SBR = 0.45: 82: 15: 2: 100: 1: 1.2.
[0086] 0.45 parts of CMC, 82 parts of deionized water, 15 parts of CNT, 2 parts of conductive glue, 100 parts of graphite, 1 part of SP, and 1.2 parts of SBR are mixed evenly.
[0087] Preparation of electrolyte: lithium salt LiPF6 and solvent (including DMC, EMC, EC and PC), additives (including VC, PE, FEC, DTD, PS and TVSi) are uniformly mixed to obtain an electrolyte, wherein, by weight, LiPF6:DMC:EMC:EC:PC:VC:PE:FEC:DTD:PS:TVSi=6.5:50:9:2.8:13.8:0.2:9:12:0.5:1.2:0.4.
[0088] Battery Assembly:
[0089] The positive electrode material is coated on the positive electrode sheet (aluminum foil), and the negative electrode slurry is coated on the negative electrode sheet (copper foil). The coating parameters of the positive and negative electrodes are: surface density 17.3mg / cm 2 , compacted density 1.6g / cm 3 , thickness 0.047mm. Figure 1 It is a surface morphology picture of the positive electrode sheet of Example 1 of the present application. Subsequently, the positive electrode sheet, the negative electrode sheet and the electrolyte are wound into a cylindrical battery.
[0090] Comparative Example 1: The procedure of adding material B to material D step by step for mixing is changed to adding material B to material D all at once for mixing, that is, step 5) and step 6) are combined into one step, and other conditions are the same as those in Example 1.
[0091] Comparative Example 2: Instead of mixing lithium iron manganese phosphate and lithium nickel cobalt manganese oxide first and then mixing with SP, lithium iron manganese phosphate, lithium nickel cobalt manganese oxide and SP are mixed together, that is, step 3) and step 4) are combined into one step, and other conditions are the same as in Example 1.
[0092] Comparative Example 3: Instead of mixing PVDF and NMP first and then mixing them with CNT, PVDF, NMP and CNT are mixed together, that is, step 1) and step 2) are combined into one step, and other conditions are the same as in Example 1.
[0093] Comparative Example 4: In step 5, the dispersion speed is 30 rpm for revolution and 1000 rpm for rotation, and other conditions are the same as those in Example 1.
[0094] Comparative Example 5: The ultrasonic frequency during the preparation of the positive electrode material was changed to 5 kHz, and other conditions were the same as those in Example 1.
[0095] For the positive electrode material of Comparative Example 1, the composite effect of lithium iron manganese phosphate on lithium nickel cobalt manganese oxide is poor, the slurry has agglomeration phenomenon, and the adhesion of the pole piece is poor. For the positive electrode material of Comparative Example 2, the composite effect of lithium iron manganese phosphate on lithium nickel cobalt manganese oxide is poor, the slurry has agglomeration phenomenon, and the internal resistance of the battery is high. For the positive electrode material of Comparative Example 3, the dispersion of slurry material B is poor, and the DCR is large during the battery cycle. For the positive electrode material of Comparative Example 4, large particles exist in the slurry, and there are particles and pitting on the surface of the pole piece, and the safety performance of the battery such as overcharge and over-discharge cannot be passed. For the positive electrode material of Comparative Example 5, the slurry has agglomeration phenomenon, poor dispersion, and poor battery rate performance.
[0096]
[0097] The steps of each test item are as follows:
[0098] Peeling force test: Use an electronic tensile testing machine to test the peeling of the material on the surface of the pole piece at a speed of 250mm / min, a test time of 36.2s, and a maximum deformation of 150mm.
[0099] Battery AC internal resistance (DCR) detection: Use the Nebula lithium-ion battery test cabinet to charge the battery to 100% SOC, then discharge it to 50% SOC and let it stand for 1 hour. Then discharge it at 1C for 30S and calculate the battery AC internal resistance.
[0100] Overcharge and over-discharge test: According to the national standard GB31241-2022, if the battery is charged to 6.3V at 1C and does not catch fire or explode, it has passed the overcharge test. If the battery is discharged to 2V at 1C and does not catch fire or explode, it has passed the over-discharge test. If the battery catches fire or explodes, it has failed the overcharge and over-discharge test.
[0101] 5C rate performance test: According to the national standard GBT31486-2015, charge to 4.2V at 2C at room temperature, let stand for 1 hour, and discharge to 2.5V at 5C. The discharge capacity must be no less than 80% of the initial capacity to pass the test.
[0102] The above contents are further detailed descriptions of the present application in combination with specific implementation methods, and it cannot be determined that the specific implementation of the present application is limited to these descriptions. For ordinary technicians in the technical field to which the present application belongs, several simple deductions or substitutions can be made without departing from the concept of the present application.
Claims
1. A method for preparing a composite positive electrode material of lithium manganese iron phosphate and nickel cobalt lithium manganese oxide, characterized in that: The preparation method comprises: Prepare raw materials, the raw materials include active materials, conductive agents, binders and solvents, the active materials include lithium manganese iron phosphate and lithium nickel cobalt manganese oxide, and the conductive agents include carbon nanotubes and SP; preparing a first solution by mixing the binder and the solvent to obtain the first solution; preparing a first mixed material, adding the carbon nanotubes into the first solution and mixing them to obtain the first mixed material; preparing a second mixed material by mixing lithium iron manganese phosphate and lithium nickel cobalt manganese oxide to obtain the second mixed material; preparing a third mixed material by mixing the second mixed material and SP to obtain the third mixed material; Preparing a fourth mixed material: adding the first mixed material to the third mixed material, mixing them evenly, to obtain the fourth mixed material, i.e., the positive electrode material; in: At least one of the steps of preparing the first solution, preparing the first mixed material, preparing the second mixed material, preparing the third mixed material and preparing the fourth mixed material is performed in a vacuum environment; In at least one of the steps of preparing the first solution, preparing the first mixed material, preparing the second mixed material, preparing the third mixed material and preparing the fourth mixed material, mixing is performed by ultrasonic treatment.
2. The preparation method according to claim 1, characterized in that: The vacuum degree of the vacuum environment is -5MPa to -1MPa.
3. The preparation method according to claim 1 or 2, characterized in that: The frequency of the ultrasound is 10kHz to 20kHz.
4. The preparation method according to claim 3, characterized in that: In the step of preparing the fourth mixed material, the first mixed material is added to the third mixed material in 2 to 4 portions.
5. The preparation method according to claim 1, characterized in that: In at least one of the steps of preparing the first solution, preparing the first mixed material, preparing the second mixed material, preparing the third mixed material and preparing the fourth mixed material, mixing is also performed by stirring, and the stirring rate is 1000rpm to 4000rpm, and the processing time is 0.1h to 3.5h.
6. The preparation method according to claim 5, characterized in that: A double planetary agitator is used for stirring, with an orbital speed of 5 to 50 rpm and a rotational speed of 1000 to 4000 rpm.
7. The preparation method according to claim 1, characterized in that: The mass ratio of the lithium manganese iron phosphate to the lithium nickel cobalt manganese oxide is 1:9 to 9:1, the D50 of the lithium manganese iron phosphate is 1 to 5 μm, and the D50 of the lithium nickel cobalt manganese oxide is 5 to 20 μm.
8. A positive electrode material prepared by the preparation method according to any one of claims 1 to 7.
9. A positive electrode, characterized in that The positive electrode includes a positive electrode collector and the positive electrode material according to claim 8 attached to the positive electrode collector.
10. A battery, characterized in that: The battery comprises the positive electrode according to claim 9.
Citation Information
Patent Citations
Lithium ion battery anode slurry mixing method, the produced anode and battery
CN101136467A
High rate lithium iron phosphate cell and preparation method thereof
CN102403531A
Lithium ion battery anode functional coating and preparation method thereof
CN102757700A
Rapidly discharged / charged high power lithium ion battery and manufacturing method thereof
CN108306013A